Concepts and treatment for diabetes among traditional and faith healers in the Northern Province, South Africa - K Peltzer; LB Khoza; ME Lekhuleni; SN Madu; VI Cherian; L Cherian (AOSIS, 2001)
The purpose of the study was to assess the concepts and treatment modalities for diabetes among traditional and faith healers in the Northern Province in South Africa. The sample consisted of 50 traditional healers (13 females and 37 males) and 50 faith healers (12 females and 38 males). They were interviewed on local terminology, clinical manifestations, causes, curability, and treatment for diabetes, help-seeking behaviour of diabetes patients, and the healers' sources of information about diabetes. Results indicate that all healers were familiar with "diabetes", however, not all of them had seen patients suffering from diabetes. The perceived causes of diabetes by both traditional and faith healers could be divided into (1) diet (especially too much of sugar), (2) heredity, (3) supernatural, and (4) psychological causes. Most traditional healers (92%) and faith healers (90%) indicated that diabetes is curable. Treatments used by the healers in this study included the use of prayer, diet, and herbs. The authors conclude that the concepts and treatment modalities for diabetes among traditional and faith healers should be taken note of by health workers while developing health education programmes in the Province.